Analysis of Factors that Influence Muzakki's Decision to Donate to Zakat Institutions: Study in the Muslim Community of Yogyakarta City - Sutrisno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of this research is to analyze the factors that influence donors' decisions in donating to the Muslim community in Yogyakarta City, This research uses quantitative methods. Sampling in this study used a purposive sampling technique, then data collection was carried out through questionnaires by distributing Google Forms to a total of 200 respondents. Statistical tests use Smart-PLS software version 3.2.9 through outer model and inner model tests. The results of this research prove that service factors do not influence the decision to donate to zakat institutions in Yogyakarta City. The reputation factor does not influence the decision to become a customer of Bank Syariah Indonesia in Batam City. Meanwhile, the religiosity factor influences donors' decisions to donate to zakat institutions in Batam City. Apart from that, the service, reputation, promotion and religiosity factors are based on an R-Square value of 0.70, which means that it influences the donors' decision to donate to zakat institutions in Yogyakarta City by 70%, the rest is influenced by other factors not included in this research.